ANALISIS POLA PENGGUNAAN LAHAN DI DAERAH ALIRAN SUNGAI (DAS) SA’DAN KABUPATEN TANA TORAJA - Dawy, D Maemunah (Bumi Lestari; Vol 7 No 2)
The purposes of this research are to know the land use pattern. To analyze the potency of land to determine the optimal land use pattern in relation, with the management of Sa’dan Watershed at Tana Toraja Regency, The research is carried out at at Sa’dan watershed of Tana Toraja Regency which include 24 villages. The methods used are qualitative and quantitative descriptive. The primary data is collected by survey or mapping method and questionnaire, meanwhile the secondary data is obtained from related departments. The colleted data are then analyzed by statistical and Geographical information System (GIS). The result of the analysis show that; 1) The condition of land use pattern at Sa’dan watershed has changed its function; 2) the degradation of land causing erosion is ampunt of 64.053,69 ton/ha/year; 3) the implementation for the change of land use pattern recommended is reducing the erosion quantity in each treatment, namely 281,19 ton/ha/year, 276,87 ton/ha/year, 4.201,66 ton/ha/year and 383,40 ton/ha/year in the first, second, third and fourt freatments. Based on the analysis result, some effort could be done in order to reduce the land degradation and the optimal land use were as follws; 1) the land use pattern should be changed: 2) the land conservation system should be implemented exaltly and quickly; and 3) the participation of the government, private sector, nongovernment social organozation, and society in relative to the management of Sa’dan W atershed of Tana Toraja Regency should be also involved.
Keywords: GIS